Infliximab trough levels are associated with endoscopic healing but not with transmural healing at one year treatment with infliximab in pediatric patients with Crohn’s disease - Choi, So Yoon; Kwon, Yiyoung; Choi, Sujin; Lee, So Mi; Choe, Byung-Ho; Kang, Ben (Frontiers in Immunology, 2023)
It is well known that infliximab (IFX) trough levels (TLs) are associated with endoscopic healing (EH) in Crohn's disease (CD). We investigated whether IFX TLs are associated with transmural healing (TH) in pediatric patients with CD following 1-year treatment. Pediatric patients with CD treated with IFX were included in this single-center prospective study. IFX TL tests, magnetic resonance enterography (MRE), and colonoscopies were simultaneously conducted after 1-year IFX treatment. TH was defined as a wall thickness of ≤3 mm without inflammatory signs evaluated using MRE. EH was defined as a Simple Endoscopic Score for Crohn's disease of <3 points on colonoscopy. Fifty-six patients were included. EH and TH were observed in 60.7% (34/56) and 23.2% (13/56) of patients, respectively. IFX TLs were higher in patients with EH (median, 5.6 vs. 3.4 µg/mL, P = 0.002), whereas IFX TLs showed no significant difference in patients with and without TH (median, 5.4 vs. 4.7 µg/mL, P = 0.574). No significant difference was observed in EH and TH between patients whose intervals were shortened or not. Multivariate logistic regression analysis showed that IFX TLs and disease duration to IFX initiation were associated with EH (odds ratio [OR] = 1.82, P = 0.001, and OR = 0.43, P = 0.02, respectively). In pediatric patients with CD, IFX TLs were associated with EH but not with TH. Further studies investigating long-term TH and proactive dosing based on therapeutic drug monitoring may clarify whether an association between IFX TLs and TH exists.